2023
DOI: 10.1021/jacs.2c13336
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Static and Dynamic Disorder in the Mixed-Metal Chalcohalide Sn2SbS2I3

Abstract: Chalcohalide mixed-anion crystals have seen a rise in interest as "perovskite-inspired materials" with the goal of combining the ambient stability of metal chalcogenides with the exceptional optoelectronic performance of metal halides. Sn 2 SbS 2 I 3 is a promising candidate, having achieved a photovoltaic power conversion efficiency above 4%. However, there is uncertainty over the crystal structure and physical properties of this crystal family. Using a first-principles cluster expansion approach, we predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Sn 2 SbS 2 I 3 has already been studied with DFT by Kavanagh et al and Nicolson et al, which provides us with an opportunity to validate our computational approach. Our PBEsol results for the energy differences between the Cmc 2 1 and P 2 1 / c phases and the Cmcm phase are reported in Table and are in good agreement with the optB86b-vdW results of Kavanagh and Nicolson.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Sn 2 SbS 2 I 3 has already been studied with DFT by Kavanagh et al and Nicolson et al, which provides us with an opportunity to validate our computational approach. Our PBEsol results for the energy differences between the Cmc 2 1 and P 2 1 / c phases and the Cmcm phase are reported in Table and are in good agreement with the optB86b-vdW results of Kavanagh and Nicolson.…”
Section: Resultsmentioning
confidence: 90%
“…Over the past four decades, the M­(II) 2 M­(III)­Ch 2 X 3 material spacelead-free as well as lead-basedhas only scarcely been explored (both theoretically and experimentally), and only a few compounds are known such as Sn 2 SbS 2 I 3 , ,,, Sn 2 SbSe 2 I 3 , Sn 2 BiS 2 I 3 , Pb 2 SbS 2 I 3 , and Pb 2 BiS 2 I 3 . , X-ray diffraction (XRD) revealed that M­(II) 2 M­(III)­Ch 2 X 3 materials crystallize predominantly in an orthorhombic Cmcm space group. , For Sn 2 SbS 2 I 3 , density functional theory (DFT) calculations demonstrated that this Cmcm structure has to be interpreted as an average over energetically more favorable, lower symmetry Cmc 2 1 configurations . XRD measurements by Doussier et al further found that Pb 2 SbS 2 I 3 changes to a monoclinic P 2 1 / c structure below 100 K .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the search for alternatives, chalcohalides are quickly gaining attention as semiconductors for multiple applications. For example, quaternary lead-free Sn 2 PnS 2 I 3 (where Pn = Sb or Bi) chalcohalides display some of the most desirable features of chalcogenide and halide materials, including direct, visible band gaps (<1.6 eV). Following their original discovery and crystallographic determination, these materials have earned renewed interest in photovoltaics, thermoelectrics, and catalysis applications. Furthermore, based on preliminary solar devices, tin chalcohalides are believed to exhibit inherently high stability and power conversion efficiency (PCEs), highlighting their potential as valuable materials for energy conversion. , …”
mentioning
confidence: 99%
“…In combination with a halide anion, this lone-pair cation leads to small effective masses for electrons and holes, defect tolerance, and strong dielectric screening. , A wide range of compounds comprising Pb 2+ , Sn 2+ , Ge 2+ , Sb 3+ , and Bi 3+ cations containing ns 2 electronic configurations are currently of interest as light harvesters . Among them, chalcohalide PIMs have emerged as promising materials having an ns 2 electronic configuration as well as a cation–halide combination. ,, Recently, Nie et al have synthesized a solar cell based on tin–antimony sulfoiodide (Sn 2 SbS 2 I 3 ) using a single-step, solution-based chemical deposition process, exhibiting a power conversion efficiency (PCE) of 4.04%. They have also demonstrated its stability against air, moisture, and light illumination.…”
mentioning
confidence: 99%